The Frame of Domestic Violence during The COVID-19 Pandemic - Selma Kirana Haryadi; Dadang Rahmat Hidayat; Rinda Aunillah Sirait (Jurnal Wanita dan Keluarga, 2022)
This study is conducted to find out how Magdalene.co as an alternative, gender sensitive media frames the issue of domestic violence during the COVID-19 pandemic. They use the victim’s perspective in reporting domestic violence amidst mainstream media’s tendencies to objectify victims and use sensationalism as a news frame. The study will be examined with a framing analysis method that explores four dimensions, namely problem definition, causal interpretation, moral evaluation and treatment recommendation, by using the theory concept of gender sensitive journalism and alternative media. This research is expected to help us identify and evaluate the role of alternative, gender sensitive media in reporting gender issues at critical times. The results showed that Magdalene.co is on the side of the victim by implementing the role of advocacy journalism, providing solutions, reviewing the root causes of domestic violence and explaining how pandemic situations hampered domestic violence services institutions to work in handling cases and made it difficult for victims to access help. Magdalene.co also has a unique standing point in framing conflict management aspects of domestic violence, because it discusses the importance of perpetrator’s rehabilitation instead of focusing solely on handling victims.